Revitalização pulpar: uma alternativa de terapêutica endodôntica para dentes com rizogênese incompleta e necrose pulpar – revisão de literatura - MARQUES, Rodrigo Fonseca (2018)
Pulp revitalization can be defined as the differentiation of progenitor cells from the apical portion of young teeth that begin to colonize the root canal, resulting in deposition of mineralized tissue on the dentin walls, aiming at reestablishing pulp vitality and continuity in root development . This procedure is currently indicated for young teeth with incomplete rhizogenesis as an alternative to the traditional apicification treatment. Apicification consists of the insertion of long-term calcium hydroxide paste into the root canal to induce the formation of a calcified barrier. Although the therapy is more classically employed, the permanence of this medication for long periods can lead to fragility of the root walls due to hygroscopic and proteolytic properties of calcium hydroxide. In view of this, there is a constant search for new treatment alternatives that allow the complete development of roots without becoming fragile. Revitalization emerged as a new option for the treatment of young teeth with pulp necrosis, using therapeutic techniques such as: induction of clot formation within the root canal, application of polyanthiotic pulps, always aiming at the neoformation of pulp tissue, which it would take the radicular complementation in length, also the increase of its thickness, giving it greater resistance. Recently, studies show the "Scaffolds" as a promise of another alternative for the situation in question, since they have the function of providing support for cell growth. It is the objective of this literature review to present a literature pertinent to the mechanism of pulp revitalization, as well as, to address in general the emergence of another regenerative alternative through the “scaffolds”.